Multi-Modal Homing in Sea Turtles: Modeling Dual Use of Geomagnetic and Chemical Cues in Island-Finding - Endres, Courtney S.; Putman, Nathan F.; Ernst, David A.; Kurth, Jessica A.; Lohmann, Catherine M. F.; Lohmann, Kenneth J. (Frontiers in Behavioral Neuroscience, 2016)
Sea turtles are capable of navigating across large expanses of ocean to arrive at remote islands for nesting, but how they do so has remained enigmatic. An interesting example involves green turtles (Chelonia mydas) that nest on Ascension Island, a tiny land mass located approximately 2000 km from the turtles’ foraging grounds along the coast of Brazil. Sensory cues that turtles are known to detect, and which might hypothetically be used to help locate Ascension Island, include the geomagnetic field, airborne odorants, and waterborne odorants. One possibility is that turtles use magnetic cues to arrive in the vicinity of the island, then use chemical cues to pinpoint its location. As a first step toward investigating this hypothesis, we used oceanic, atmospheric, and geomagnetic models to assess whether magnetic and chemical cues might plausibly be used by turtles to locate Ascension Island. Results suggest that waterborne and airborne odorants alone are insufficient to guide turtles from Brazil to Ascension, but might permit localization of the island once turtles arrive in its vicinity. By contrast, magnetic cues might lead turtles into the vicinity of the island, but would not typically permit its localization because the field shifts gradually over time. Simulations reveal, however, that the sequential use of magnetic and chemical cues can potentially provide a robust navigational strategy for locating Ascension Island. Specifically, one strategy that appears viable is following a magnetic isoline into the vicinity of Ascension Island until an odor plume emanating from the island is encountered, after which turtles might either: (1) initiate a search strategy; or (2) follow the plume to its island source. These findings are consistent with the hypothesis that sea turtles, and perhaps other marine animals, use a multi-modal navigational strategy for locating remote islands.